REDEFINING PUNISHMENT AS A MEANS OF DISCIPLINE IN SCHOOLS: AN EXAMPLE FROM KOPANO MATLWA’S SPILT MILK - DARE, S.O.; ADENIRANYE, A.C. (Journal of Education and Practice, 2022)
Purpose: Punishment has been used by authorities of schools as a means of instilling discipline in the school. The nature and type of punishment used vary from one school to another. Some are utilitarian while others are retributive. In most Nigerians schools, especially the public schools, the latter holds. As a result of this students have not shown any meaningful change in behaviour and this highlights the failure of the structure of discipline in our schools. This study aims to consider a redefinition of the nature of the punishment structure used in schools as presented in literary text. Methodology: The data for the study were gathered from Kopano Matlwa's Spilt Milk. Instances of punishment meted out to erring students in a school were descriptively analysed with a view to determining the nature and informing philosophy behind them. The study also seeks to seek the gains or otherwise of the nature of punishment used to discipline students in the text. Findings: The study discovered that the nature of punishment given to students is reformative and utilitarian against the retributive nature of punishment used in the Nigerian structure. It is also more dignifying and less dehumanising for the student-offenders but of most importance is that students acquire more knowledge especially around the type of their offence. Parents are also more receptive of this type of punitive measures and encourage that it be used in the school. Unique Contribution to theory, practice and policy: The study recommended that government should legislate on the present structure of punishment in most Nigerian schools to allow for punishments that are more reformative and utilitarian in nature. School authorities should adopt the positive-oriented methods that are philosophically utilitarian.